Tinjauan Yuridis Tindak Pidana Child Grooming terhadap Anak Melalui Media Sosial serta Perlindungan Hukumnya: Studi Kasus Aurelie Moeremans - Mia Suhermawati; Makmur Makmur; Rizal Muhammad Faisal (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The rapid development of social media has increased the risk of child grooming, a form of psychological manipulation aimed at gaining a child's trust prior to sexual exploitation. This study aims to examine the regulation of child grooming under Indonesian positive law, analyze the legal protection afforded to child victims, and assess the juridical aspects of the Aurelie Moeremans case. This research employed a normative legal method using statutory, conceptual, and case approaches. Legal materials were collected through library research and analyzed using descriptive qualitative methods. The findings indicate that Indonesian positive law has not specifically regulated child grooming as an independent criminal offense, resulting in legal gaps, particularly during the pre-exploitation stage. Existing legal protection for victims remains inadequate due to fragmented regulations and evidentiary challenges. Therefore, a comprehensive legal framework is required to strengthen legal certainty and improve the protection of children against child grooming through social media.